8 The Statutes at Large, from the Twelfth Year of King Charles II, to the Last Year of King James II 40 (Danby Pickering ed. 1763) - (:unkn) unknown (My University, 1662)
1662 Militia Act: Ordered the king's agents to search for and seize all arms in the custody or possession of any person "judge[ d] dangerous to the peace of the kingdom."
Keywords: POSSESSION - DANGEROUS PERSONS